Briquetas con cascarilla de aguaje (Mauritia flexuosa) más papel reciclado y almidón en Iquitos 2023 - Pilco Rojas, Yolanda Obdulia (2024)
The production of briquettes from aguaje husk was conducted in the germplasm area of agronomy (Agrostology Garden). The study employed a quantitative approach and an experimental design, with a population comprising 16 briquettes prepared according to specified treatments. The aim was to manufacture briquettes using the mentioned input along with paper and yucca starch, serving as binding agents. To assess the efficiency of the briquettes, a grilling stove was fabricated. The conclusion was drawn that the fourth treatment (50% aguaje husk + 40% paper + 10% yucca starch) yielded the best averages, with values of 30 centimeters (length), 120 grams (weight), 9 centimeters (diameter), taking 7 minutes to ignite, and 15 minutes for water to boil. Consequently, the alternative hypothesis is accepted as one of the treatments (T4) exhibited superior results in all variables.